Digitizing medieval manuscripts : the St. Chad gospels, materiality, recoveries, and representation in 2D & 3D /: the St. Chad gospels, materiality, recoveries, and representation in 2D & 3D. (2019) - Endres, Bill, 1962-
No abstract available